Performance of High Strength Concrete Containing Treated Fine Metakaolin, Palm Oil Fuel Ash, and Coal Bottom Ash as Substitute Materials Toward Compressive Strength and Flexural Strength Test - Mohd Nizam, Mohammad Amirul; Ismail, Mohd Hanif; Che Rahim, Nur Anis Natasha; Abu Bakar, Muhammad Nur Rasyid (Journal of Structural Monitoring and Built Environment, 2023)
The annual increase in cement use has a detrimental effect on the environment. To lessen the harmful effects on the environment, concrete production now incorporates industrial waste from power plants such as coal bottom ash and palm oil fuel ash (POFA). In order to create more environmentally friendly concrete, this study used metakaolin (MK), palm oil fuel ash (POFA), and coal bottom ash (CBA). The purpose of this study is to determine how these substitute materials affect the compressive and tensile strengths of concrete. MK and POFA are partial cement replacements, whereas CBA is a partial sand replacement. The compressive and flexural strengths of the concrete were assessed to determine the impact of these materials on its strength. The trials used 20% MK and 10% CBA as the constants and 5%, 10%, 15%, and 20% POFA as cement substitutions for the variables. The concrete with a 10% POFA replacement had the highest compressive strength (78 MPa) and flexural strength (7.5 MPa) among the other concrete mixes while having the best workability.